O constructo narratológico do livro-imagem: um estudo de obras premiadas pela FNLIJ (2010-2020) - Silva, Evelin Gomes da (2024)
ABSTRACT How is the narrative of a picture book constituted? This is the main question of this documentary research with a deductive aspect, with a descriptive-explanatory approach. In this thesis, we establish correspondences between Literature, Visual Arts and Cinema, from the perspective of literary theory, image theory and interarts studies. Our object of study are works awarded between 2010 and 2020, in the “Image” category, by the National Children's and Youth Book Foundation (FNLIJ), which brings together 10 national and international authors. As an elementary premise, we present the conceptualization of the “picturebook” terminology, adopted in this work, as well as the identification, description and interpretation of the construct of fictional discourse of image productions with a view to highlighting their narratological potential. When describing the structural elements of a narrative, we use conceptual frameworks and figures, taking as input the reflections of Genette (1979), Todorov (1979), D’Onofrio (1995), McKee (1997), Culler (1999), Xavier (2003), Franco Júnior (2003), Aumont (2004), Gancho (2006) and Ceia (2009a). For the systematic organization and functions of images, we resorted to the theories of Jakobson (1976), Chalhub (1999) and Camargo (1998; 2014). Furthermore, studies regarding aesthetic pregnancies in works aimed at children and young people were essential (Oliveira, 2008a), the functions and endless possibilities that the “reading” process can provide to readers (Nikolajeva; Scott, 2006) and the implicit elements present in the sequential composition of the images, as well as their strategic implications for establishing the message (Navas; Ramos, 2021). To explain in detail each of the singularities of composition and possible meanings present in the image books analyzed, we used the essence of the poetic constitution of rhetoric from ekphrasis (Vieira, 2016; Medina, 2010; Hansen, 2006), which helped us in identification and description of the image elements that make up the diegesis. Our research included studies by Manguel (2001), Oliveira (2008b), Nikolajeva and Scott (2011), Van der Linden, (2011), Ramos (2020) and Belmiro (2014), which highlight the illustrator's creation and the importance of graphic design. This tool, in turn, plays an active role in constructing the sense of narrative, whether in relation to format, material, arrangement of elements in the scene that create the sensation of movement, pause or continuity, typography, spaces blanks that can suggest emptiness, silence, reflection or emotional isolation of the dramatic figures in the plot etc. To understand the challenges and strategies of authors to tell stories only with images, were essential the discussions promoted by Kiefer (1995), Azevedo (2005), Nikolajeva and Scott (2006), Kress and Leeuwen (2006), Ribeiro (2007), Oliveira (2008), Biazetto (2008), Paiva (2010), Van der Linden (2011), Painter, Martin and Unsworth (2012), Serafini (2014), Ramos (2020), Navas (2020), Gutfreund (2022), Cecilia Bajour (2023) and Lima (2023). To understand the challenges and strategies of authors to tell stories only with images, we present the discussions promoted by Kiefer (1995), Azevedo (2005), Nikolajeva and Scott (2006), Kress and Leeuwen (2006), Ribeiro (2007), Oliveira (2008), Biazetto (2008), Paiva (2010), Van der Linden (2011), Painter, Martin and Unsworth (2012), Serafini (2014), Ramos (2020), Navas (2020), Gutfreund (2022), Cecilia Bajour (2019; 2023) and Lima (2023). As a final analysis, we demonstrate the singularities of works that permeate aspects of the Hero's Journey, focusing on studies by Campbell ([1989], 2007) and Vogler (2006). This approach was chosen since 70% of the corpus reinforces this theme. Therefor, by demonstrating how the narratological and aesthetic construct of FNLIJ's image books was constituted, we highlight their polysemic and interpretative potential, which expands discussions in Literature, providing new perspectives for future studies on image narratives.